Integrating AI/ML-Powered Predictive Analytics into Data Protection Strategies - Sadhu, Sravan Kumar (International Journal of Computing and Engineering, 2025)
The integration of artificial intelligence and predictive analytics represents a transformative paradigm shift in organizational data protection strategies, moving beyond traditional reactive methodologies toward proactive, intelligent frameworks that anticipate and prevent failures before they manifest. Modern enterprises face unprecedented challenges with exponential data growth, increasingly complex IT infrastructures, and evolving threat vectors that render conventional backup and disaster recovery approaches insufficient for maintaining continuous availability and minimal data loss tolerance. Machine learning algorithms demonstrate remarkable capabilities in predicting backup job failures, optimizing resource allocation, and reducing false positive alerts through sophisticated pattern recognition and anomaly detection mechanisms. Time-series forecasting models, classification algorithms, and advanced neural networks enable organizations to automate routine tasks, enhance operational efficiency, and significantly improve system reliability. The economic impact of implementing predictive analytics extends beyond cost reduction to encompass substantial improvements in service level agreement adherence, mean time to resolution, and overall infrastructure resilience. Organizations adopting these technologies experience transformative benefits, including enhanced backup success rates, reduced administrative overhead, optimized resource utilization, and proactive maintenance scheduling capabilities. The evolution toward edge computing integration and quantum computing implications promises further advancements in predictive capabilities, while comprehensive implementation frameworks ensure successful deployment across diverse enterprise environments through systematic maturity assessment, organizational change management, and continuous improvement processes.